Strategi Komunikasi dalam Penanganan Keluhan Pelanggan pada Industri Keramik: Studi Kasus di PT Primarindo Argatile - Nofalia Juliana Sari; Eka Susilawati; Fithrotul Kamilah; Noerma Kurnia Fajarwati; Arfian Suryasuciramdhan (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Handling customer complaints is a crucial aspect of maintaining loyalty, especially in manufacturing industries such as ceramics. PT Primarindo Argatile faces various complaints from agents, particularly regarding product defects and delivery issues. This study aims to examine the communication strategies implemented by the company in addressing complaints and to identify the challenges encountered in the process. The research uses a qualitative method with a case study approach, collecting data through in-depth interviews and documentation of customer complaints over the past six months. The results show that the company’s communication strategy has been systematically designed, emphasizing openness, empathy, and professionalism. The company implements a standard operating procedure (SOP) for handling complaints, utilizes multiple communication channels (telephone, WhatsApp, email, and social media), and conducts regular evaluations to improve services. Within the CRM framework, this communication strategy includes the role of marketing staff in building relationships (people), the application of SOPs and follow-up procedures (process), and the use of digital technology (technology). Nevertheless, several obstacles remain, including differences in understanding due to technical terminology, emotional challenges when customers are upset, time constraints caused by internal procedures, customer dissatisfaction despite provided solutions, and inconsistent responses among staff.